Outcomes after delirium in a Japanese intensive care unit - Yamaguchi, Takako; Tsukioka, Etsuko; Kishi, Yasuhiro (General hospital psychiatry, 2014)
Delirium in the intensive care unit (ICU) is recognized as a major public health problem. Few Japanese outcome studies have been reported. The purpose of the study was to investigate the hospital outcomes of ICU delirium in a Japanese general hospital. Patients were drawn from consecutive admissions to an ICU at a tertiary care university hospital. Delirium assessments were conducted using the Intensive Care Delirium Screening Checklist (ICDSC). The following information was recorded: age, sex, the reason for ICU admission, the ICDSC scores, the COmplexity PRediction Instrument (COMPRI) scores, the length of stay (LOS) in the ICU, the total hospital LOS, hospital outcomes and social worker’s consultation. Of the 126 patients who were evaluated, 35 (27.8%) developed delirium during the ICU stay. Older age and biopsychosocial vulnerability assessed by the COMPRI were risk factors of ICU delirium. ICU delirium was a predictor of increased mortality and associated with prolonged ICU and hospital LOS. ICU delirium was an independent risk factor for having social worker’s consultation after ICU discharge. ICU delirium is associated with worse outcomes including mortality and LOS in Japan. ICU delirium is independently associated with further social worker’s consultations, suggesting that early proactive social worker’s intervention may be beneficial for the patients with ICU delirium.